Second-Hand Smoke and Early Allergic Manifestation in Children - Sitisalma Amirah Dzakiyyah; Anang Endaryanto; Linda Dewanti; Azwin Mengindra Putera; Anisa Ayu Maharani (Jurnal Respirasi, 2022)
Introduction: The interaction between genetic and environmental factors plays an important role in shaping the early development of allergies, including exposure to cigarette smoke. This study aimed to determine the relationship between second-hand smoke exposure and early allergic manifestations in children. Methods: This was an observational analytic study with a cross-sectional design. Pediatric patients who suffered from allergies in the allergy outpatient clinic at the Department of Pediatrics, Dr. Soetomo General Hospital, Surabaya were included in this study. Data were obtained through medical records. Results: This study involved 190 patients and showed that 50% of the patients have families who smoke at home, the most common early manifestations were at 11-20 months old (32.10%), and the most common early manifestations were respiratory manifestations (98.42%). There was a significant relationship between the presence of a family member who smoked at home with the age of early manifestation, respiratory manifestation, and skin manifestation in allergic pediatric patients (all p < 0.05). There was no significant relationship between the presence of family members who smoked at home with gastrointestinal manifestations in allergic pediatric patients (p = 0.301). Conclusion: There was a significant relationship between the presence of family members who smoke at home with age, respiratory tract, and skin manifestations in allergic pediatric patients.